Comparison of ranibizumab and subthreshold micropulse laser in treatment of macular edema secondary to branch retinal vein occlusion. Issue 6 (November 2018) - Buyru Özkurt, Yelda; Akkaya, Sezen; Aksoy, Sibel; Şimşek, Mert Hakan
Purpose: To compare the effects of intravitreal ranibizumab injection and yellow (577 nm) subthreshold micropulse laser treatment in patients with macular edema following non-ischemic branch retinal vein occlusion. Methods: The medical records of 51 patients who underwent intravitreal ranibizumab (0.5 mg) injection or subthreshold micropulse laser for the treatment of macular edema due to branch retinal vein occlusion were retrospectively reviewed. Subthreshold micropulse laser was administered with a 10% duty cycle, 100 μm spot diameter, 200 ms exposure time. The patients received an injection or laser treatment at baseline and were, then, retreated as needed and were followed for 12 months. The mean best corrected visual acuity changes over the follow-up and the decrease in the mean central macular thickness were evaluated. Results: A total of 27 and 24 patients were assigned to intravitreal ranibizumab and subthreshold micropulse laser subgroups, respectively. The mean number of treatment was 3.81 of intravitreal ranibizumab group and 1.5 of subthreshold micropulse laser group (p < 0.05). The subgroups were similar with regard to the mean score of best corrected visual acuity at baseline, at 1, 6, and 12 months (p > 0.05). The decrease in the mean central macular thickness was significant in both intravitreal ranibizumab and subthreshold micropulse laser groups at 1, 6, and 12 months than that of values at baseline (p < 0.05). No new ocular or systemic adverse events were observed. Conclusion: Our study results showed that intravitreal ranibizumab or yellow subthreshold micropulse laser treatment for macular edema due to branch retinal vein occlusion was not found to be superior to each other for reducing macular thickness and increasing visual acuity for 1-year period. Based on these results, subthreshold micropulse laser may be a useful alternative approach in the treatment of macular edema secondary to branch retinal vein occlusion.